Developing a performance evaluation scheme for engineering facilities in commercial buildings: state-of-the-art review - Lai, Joseph H. K.; Man, Chun Sing (International Journal of Strategic Property Management, 2017)
Various post-occupancy evaluation schemes have been introduced for assessing building performance but one tailored for large-scale commercial buildings remains to be seen. Intended to develop a scheme for evaluating the performance of engineering facilities in existing commercial buildings, a multi-stage study was carried out in a dense-built metropolis – Hong Kong. Reported here is the part of work based on an extensive literature review. Considering the characteristics of relevant evaluation schemes, the requirements for useful performance evaluation and the criteria for selecting key performance indicators (KPIs), an integrated process-hierarchy model was formed for identifying applicable indicators for the intended scheme. A total of 71 indicators, classified into five categories: (i) physical, (ii) financial, (iii) task and equipment related, (iv) environmental, and (v) health, safety and legal, were identified. Their representations and their empirical applications, which are helpful for the strategic management of existing buildings, are also described.